2021
DOI: 10.1097/spv.0000000000001070
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Music Listening in Pelvic Reconstructive Surgery: A Randomized Trial

Abstract: Objectives We aimed to investigate the effect of music listening on preoperative anxiety compared with usual care in patients undergoing pelvic reconstructive surgery. Methods Patients scheduled for pelvic reconstructive surgery were enrolled on the day of surgery. Participants were randomized to either the usual care (control group) or to music listening on headphones (music group) before their surgery. Participants completed the Spielberg State-Trait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The video intervention, which had focused on minor surgeries, did significantly decrease anxiety levels [23]. Another four studies explored the use of music and/or art therapy and found that the interventions significantly decreased pre-operative anxiety levels [24][25][26][27]. Two studies that explored the use of anxiolytics had mixed results, but they did find success with metoprolol for short-term perioperative anxiety [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The video intervention, which had focused on minor surgeries, did significantly decrease anxiety levels [23]. Another four studies explored the use of music and/or art therapy and found that the interventions significantly decreased pre-operative anxiety levels [24][25][26][27]. Two studies that explored the use of anxiolytics had mixed results, but they did find success with metoprolol for short-term perioperative anxiety [28,29].…”
Section: Discussionmentioning
confidence: 99%